Summary and implications - Rashid, Shahidur; Zhang, Xiaobo (International Food Policy Research Institute, 2019)
Led by aquaculture, the fishery sector in Bangladesh has been remarkably successful in rapidly increasing production, reducing prices, and meeting rising domestic demand. The trend has defied many earlier predictions, and the success clearly deserves to be labeled a Blue Revolution. In the early 1990s, when the country was celebrating the success of the Green Revolution, per capita annual fish consumption was only 10 kilograms, with widespread concerns that consumption could decline even further because of rising prices (Bouis and Haddad 1992). The policy ambition was not high even in the early 2000s. In 2005 a Food and Agriculture Organization (FAO) report argued that reaching per capita consumption of 18 kilograms per year would be a big accomplishment. The country far exceeded that target by 2010; and according to the latest estimates, per capita fish consumption in Bangladesh reached 23 kilograms per year in 2016 (BBS 2017). This book has attempted to understand the enablers, impacts, and prospects of this unprecedented growth.